Guidelines for Developing Ethical Leadership among School Administrators under Khon Kaen Primary Educational Service Area Office 5 - Thongouan, Teeradet; Ruangsuwan, Chayakan; Laamkha, Runglawun (Journal for Developing the Social and Community, 2025)
Background and Aims: In the 21st century, rapid changes in economic, social, and technological dimensions have made educational administration increasingly complex and demanding. School administrators are thus required to exhibit leadership that not only focuses on academic performance but also integrates moral consciousness, ethical integrity, and transparency to serve as role models and guide their organizations toward sustainability. This study aimed to (1) examine the current situation, desired condition, and priority needs of ethical leadership among school administrators under the Khon Kaen Primary Educational Service Area Office 5, and (2) develop suitable guidelines for enhancing ethical leadership in this context. Methodology: This study employed a research and development (R&D) design consisting of two phases. In Phase 1, the current and desired conditions and the priority needs were examined using a questionnaire administered to a sample of 311 participants, 43 school administrators and 268 teachers, selected through stratified random sampling. The data were analyzed using descriptive statistics and the Priority Needs Index (PNIModified). In Phase 2, both quantitative and qualitative data were synthesized to develop ethical leadership guidelines through in-depth interviews with six exemplary school administrators. The proposed guidelines were then evaluated for appropriateness and feasibility by nine experts. Results: The findings revealed that the overall current state of ethical leadership among school administrators was at a moderate level (= 3.49, S.D. = 0.72), while the desired condition was at the highest level (= 4.65, S.D. = 0.50). The most prioritized aspect for development was respectfulness (PNIModified = 0.39). The developed guidelines comprised five core components: honesty, responsibility, fairness, respectfulness, and trust. Expert evaluations indicated that the guidelines were highly appropriate and feasible (= 4.82, S.D. = 0.37; = 4.76, S.D. = 0.50, respectively). Conclusion: The developed guidelines for ethical leadership were comprehensive, coherent, and practically applicable to the school context. Their implementation can strengthen administrators’ morality, transparency, and accountability, serving as a key mechanism to foster moral and sustainable school organizations.